The economics of platforms - Vera Demary; Christian Rusche (Institut der deutschen Wirtschaft (IW), 2018)
Digital platforms already dominate the top 10 of the world's most valuable firms. The specific characteristics of their business model, such as quick growth and market power soon after market entry, have provoked public discourse. This paper analyzes digital platforms' business models, the reasons for their success and the challenges they present. Digital platforms offer an online forum for conducting transactions and therefore are able to dramatically reduce transaction costs, which creates value for platform users. Generally, digital platforms are aware of the high and increasing importance of data. By collecting and combining data from the different user groups, digital platforms are able to improve their service for existing users and to attract new user groups. Digital platforms' market power and their control over large, valuable sets of data have attracted the attention of regulatory authorities and led to investigations and fines. Economic policy should aim to protect consumers while still fostering the digital platform business model. – – Digitale Plattformen dominieren bereits heute die Top 10 der weltweit wertvollsten Unternehmen. Doch die spezifischen Merkmale des Plattformgeschäftsmodels, wie schnelles Wachstum und die damit erreichbare Marktmacht kurz nach Markteintritt, haben zu öffentlichen Diskussionen geführt. Die vorliegende IW-Analyse hat sich zum Ziel gesetzt, die Grundlagen des Erfolgs von Plattformen und die damit einhergehenden Herausforderungen zu analysieren. Dabei wird unter einer digitalen Plattform ein webbasierter Intermediär verstanden, der Transaktionen zu stark reduzierten Kosten ermöglicht und dadurch einen Mehrwert für Kunden generiert. Digitale Plattformen sind sich zudem der wachsenden Bedeutung von Daten bewusst. Durch das Sammeln und Kombinieren von Daten verschiedener Nutzergruppen können sie ihre Leistungen für ihre Kunden verbessern und neue hinzugewinnen. Doch die Marktmacht digitaler Plattformen und ihr Zugriff auf große, wertvolle Datensätze haben bereits zu Untersuchungen, Verfahren und Strafen geführt. Ziel der Wirtschaftspolitik in diesem Zusammenhang sollte sein, die Konsumenten zu schützen und gleichzeitig Plattformen zu fördern.
Keywords: 330